Bilateral Internal Carotid Arteries Occlusion: A Case Report - Prabhaw Upadhyaya; Prasanna Karki; Baburam Pokharel; Gopal Raman Sharma (Journal of Nepal Medical Association, 2022)
Bilateral internal carotid artery occlusion is a disease that is encountered rarely. We report a case of a 54 years old female smoker, who presented with acute onset right-sided limb weakness, facial deviation and slurring of speech. On computed tomography angiography occlusion of the bilateral internal carotid artery was seen and a high-flow collateral circulation was formed through the vertebrobasilar system. Computed tomography brain perfusion showed marked cerebral hypoperfusion on the left side. The patient was thrombolysed and kept on dual antiplatelet therapy. Post-medical treatment, motor power and speech significantly improved.